Histatin 1 enhanced the speed and quality of wound healing through regulating the behaviour of fibroblast. (13th July 2021) - Cheng, Liuhanghang; Lei, Xiaoxuan; Yang, Zengjun; Kong, Yanan; Xu, Pengcheng; Peng, Shiya; Wang, Jue; Chen, Cheng; Dong, Yunqing; Hu, Xiaohong; Zhang, Xiaorong; Forouzanfar, Tymour; et al.
Abstract: Objectives: Histatin 1(Hst 1) has been proved to promote wound healing. However, there was no specific study on the regulation made by Hst 1 of fibroblasts in the process of wound healing. This research comprehensively studied the regulation of Hst 1 on the function of fibroblasts in the process of wound healing and preliminary mechanism about it. Materials and methods: The full‐thickness skin wound model was made on the back of C57/BL6 mice. The wound healing, collagen deposition and fibroblast distribution were detected on days 3, 5 and 7 after injury. Fibroblast was cultured in vitro and stimulated with Hst 1, and then, their biological characteristics and functions were detected. Results: Histatin 1 can effectively promote wound healing, improve collagen deposition during and after healing and increase the number and function of fibroblasts. After healing, the mechanical properties of the skin also improved. In vitro, the migration ability of fibroblasts stimulated by Hst 1 was significantly improved, and the fibroblasts transformed more into myofibroblasts, which improved the function of contraction and collagen secretion. In fibroblasts, mTOR signalling pathway can be activated by Hst 1. Conclusions: Histatin 1 can accelerate wound healing and improve the mechanical properties of healed skin by promoting the function of fibroblasts. The intermolecular mechanisms need to be further studied, and this study provides a direction about mTOR signalling pathway. Abstract : Histatin 1 may be activated by G protein coupled receptors on the surface of cell membrane. Subsequently, PI3K / Akt / mTOR signaling pathway was activated to promote the migration of fibroblasts and the transformation of fibroblasts into myofibroblasts. By regulating the function of fibroblasts, it can improve the healing speed of acute wound and the mechanical properties of skin after healing.